2017
DOI: 10.1111/jvs.12521
|View full text |Cite
|
Sign up to set email alerts
|

Aspect and slope influence plant community composition more than elevation across forest–tundra ecotones in subarctic Canada

Abstract: Questions How does tree line community composition vary between elevations, aspects and slope angles in the alpine subarctic and what are the specific abiotic factors governing this variability? How do species richness and rates of community turnover vary from low to high elevation across the forest–tundra ecotone? What do the results indicate about future vegetation change? Location Kluane Region, southwest Yukon, Canada. Methods We surveyed plant communities and measured key abiotic variables across forest–t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…At our study sites, mean growing season soil temperatures did not decrease with increasing elevation as expected, but rather were coldest in the forest zone and warmest in the transition, with alpine temperatures falling between the two. Other studies (Bader, Rietkerk, & Bregt, ; Dearborn & Danby, ) have also found soil temperatures to be lower in forested relative to alpine areas, attributing the reduction in temperature to the effect of shading by forest canopies. Although based on only one year of monitoring data, the negative correlation between establishment and growing season temperatures indicates that low mean soil temperatures are not likely the primary abiotic control on regeneration beyond the treeline in our study area.…”
Section: Discussionmentioning
confidence: 84%
“…At our study sites, mean growing season soil temperatures did not decrease with increasing elevation as expected, but rather were coldest in the forest zone and warmest in the transition, with alpine temperatures falling between the two. Other studies (Bader, Rietkerk, & Bregt, ; Dearborn & Danby, ) have also found soil temperatures to be lower in forested relative to alpine areas, attributing the reduction in temperature to the effect of shading by forest canopies. Although based on only one year of monitoring data, the negative correlation between establishment and growing season temperatures indicates that low mean soil temperatures are not likely the primary abiotic control on regeneration beyond the treeline in our study area.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, permanent plots capturing variation in plant community composition due to major topographic features are needed. These plots should be surveyed and monitored dynamically at each study site (Dearborn and Danby 2017), as long-term experiments can provide invaluable datasets for identifying how species composition changes both spatially and temporally (Cleland et al 2013, Collins et al 2016.…”
Section: Factors Influencing the Plant Community Compositionmentioning
confidence: 99%
“…). Dearborn and Danby () showed that plant communities varied more significantly with the slope aspect than they did with elevation. Likewise, Sternberg and Shoshany () found that the vegetation structure within a specific site had changed significantly in the short distance separating the north and south‐facing slope aspects, which corresponded to the patterns observed in two other sites with respect to the rainfall gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the assembly rules in a forest–tundra ecotone and considered the ecological processes that are potentially at play in vegetation changes. Previous studies (e.g., Trant et al, ) have suggested that abiotic environmental conditions directly mediate vegetation displacement in the forest–tundra ecotone, and thus, these conditions may significantly affect landscape changes in response to changes in climate, which are expected to progress further (Dearborn & Danby, ). In our study, however, we found only weak evidence that tundra communities are significantly mediated by environmental factors.…”
Section: Discussionmentioning
confidence: 99%